Serum Metabolomic Profiling in a Rat Model Reveals Protective Function of Paeoniflorin Against ANIT Induced Cholestasis. (25th January 2016) - Chen, Zhe; Zhu, Yun; Zhao, Yanling; Ma, Xiao; Niu, Ming; Wang, Jiabo; Su, Haibin; Wang, Ruilin; Li, Jianyu; Liu, Liping; Wei, Zhenman; Zhao, Qingguo; et al.
Abstract : Cholestasis is a leading cause of hepatic accumulation of bile acids resulting in liver injury, fibrosis, and liver failure. Paeoniflorin displays bright prospects in liver protective effect. However, its molecular mechanism has not been well‐explored. This study was designed to assess the effects and possible mechanisms of paeoniflorin against alpha‐naphthylisothiocyanate‐induced liver injury. Ultraperformance liquid chromatography coupled with quadrupole time‐of‐flight combined with principle component analysis and partial least squares discriminant analysis were integrated to obtain differentiating metabolites for the pathways and clarify mechanisms of disease. The results indicated that paeoniflorin could remarkably downregulate serum biochemical indexes and alleviate the histological damage of liver tissue. Different expression of 14 metabolites demonstrated that paeoniflorin mainly regulated the dysfunctions of glycerophospholipid metabolism and primary bile acid biosynthesis. Moreover, several pathways such as arginine and proline metabolism, ether lipid metabolism, and arachidonic acid metabolism were also related to the efficacy. In conclusion, paeoniflorin has indicated favorable pharmacological effect on serum biochemical indexes and pathological observation on cholestatic model. And metabolomics is a promising approach to unraveling hepatoprotective effects by partially regulating the perturbed pathways, which provide insights into mechanisms of cholestasis. Copyright © 2016 John Wiley & Sons, Ltd.